Utilization of posaconazole oral suspension or delayed‐released tablet salvage treatment for invasive fungal infection. Issue 11 (November 2016) - Kim, Jong Hun; Benefield, Russell J.; Ditolla, Kali
Summary: Posaconazole may be useful for salvage treatment (ST) for invasive fungal infections (IFIs). The aim of this study was to evaluate the efficacy of posaconazole ST with either posaconazole oral suspension (SUS) or delayed‐released tablet (TAB) in patients with IFI. A retrospective review of patients who received posaconazole ST for IFI at the University of Utah Health Sciences Center between December 2007 and March 2014 was conducted. A total of 14 episodes of posaconazole ST for proven (9 episodes) and probable (5 episodes) IFI were identified in 14 patients. The median age was 54 years and the majority of patients (64.3%) had underlying haematological diseases. Posaconazole SUS and TAB were used in 11 episodes and 3 episodes respectively. The duration of posaconazole ST ranged from 28 to 370 days with a median of 65 days. Posaconazole ST with TAB achieved favourable serum posaconazole trough concentrations (median 1.4 μg mL −1 ) compared to posaconazole SUS (median 1.0 μg mL −1 ). The overall clinical success rate with posaconazole ST was 71.4% (10 of 14 episodes). One patient died of progression of IFI. Adverse events were noted in two patients. Posaconazole SUS or TAB may be used effectively for IFI ST.